ANALISIS STABILITAS HASIL GENOTIPE KEDELAI MENGGUNAKAN METODE ADDITIVE MAIN EFFECT AND MULTIPLICATIVE INTERACTION (AMMI) - Krisnawati, Ayda; Basunanda, Panjisakti; Nasrullah, nFn; Adie, M Muchlish (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
An ideal soybean cultivar is the one that achieves the greatest yield consistently across many environments regardless of environmental conditions. The objective of this experiment was to determine the soybean seed yield stability by AMMI method. A total of ten soybean genotypes, which consisted of eight soybean promising lines (G100H/SHRW-60-38, SHRW-60/G100H-73, SHRW-60/G100H-68, SHRW-60/G100H-66, G100H/SHRW-34, SHRW-60/G100H-5, SHRW-60/G100H-70, and SHRW-60/G100H-75) and two soybean check varieties (Kaba and Wilis) was evaluated at six soybean production centers in Yogyakarta, Banyuwangi and West Nusa Tenggara during 2011. The field experimental design for each location was completely randomized design with four replicates. Each genotype was planted on 2.4 m x 4.5 m plot size, 40 cm x 15 cm plant distance, with 2 plants/hill. Stability analysis on seed yield was based on the AMMI method.The combined analysis showed that the genotype and GEI were highly significant for seed yield. The AMMI of the first significant interaction principal component (PC1) accounted for 66.07% of the total variation. Based on AMMI1 biplot, G1 (G100H/SHRW-60-38) and G5 (G100H/SHRW-34) showed higher yield stability. However, the most stable genotype (G5) produced low yield. The other stable genotype (G5) showed highest soybean yield, and therefore it is proposed to be released as a new improved soybean variety.